Productivity for librarians : how to get more done in less time - Hines, Samantha S. (Chandos information professional series., 2010)
Productivity for Librarians provides tips and tools for organizing, prioritizing and managing time along worth reducing stress. The book presents a resources guide for continued learning about and exploration of productivity in relation to individual circumstances featuring motivation, procrastination and time management guidelines. Addressing the unique challenges faced by librarians the author supplies a balanced view of a variety of tools and techniques for dealing with overwork and stress.